Indoor navigation system using annotated maps in mobile augmented reality - Chia, Shu En (Universiti Malaysia Sarawak (UNIMAS), 2019)
The rapid evolution of technology in recent years make indoor navigation possible by offering a variety of alternative techniques. In this research, a prototype of a mobile AR application for indoor navigation that using the interactive annotated map is presented. It determines the user starting location via scanning the reference image which placed in a specific location. Besides, AR Core supported device is adopted in this project to blend the digital and physical worlds seamlessly by aligning the appropriate 3D path with features in the real world through ground detection. Furthermore, this app helps to reduce the human cognitive workload and save time by presenting relevant information as well as a better understanding of the surrounding. Moreover, the application implemented on Android phone with ARCore and tested at Level 1, CAIS building in UNIMAS. Finally, the result proved the application provides a good platform to show the location information without requiring hardware installation and a strong wireless connection.